Bancassurance on the Value of Banking Companies in Asia Pacific: Profitability as a Mediating Variable - Luthfia Afifah; Efa Yonnedi (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
High competition in the financial sector forces banks to increase non-interest income to be able to escape the banking crisis and compete in the global economy, one of which is through bancassurance cooperation . This research was conducted to determine the effect of bancassurance on banking firm value with profitability as a mediating variable. The research sample consisted of 142 conventional commercial banks listed on the stock exchanges of each APEC member country and available in the eikon reflective database for the 2016-2022 period which were selected by purposive sampling . Panel data regression was performed to test the direct effect, followed by the Sobel test to test the indirect effect. The results of the study show that bancassurance has a significant direct or indirect effect on the value of banking companies through bank profitability. Bancassurance commissions obtained by banks are able to increase fee-based income and generate greater bank profitability, thus encouraging an increase in the value of banking companies. Positive results of bancassurance on banking profitability and value, are expected to encourage APEC member countries to further optimize bancassurance supported by regulations from the government.